BENEFITS PERCEIVED BY DEPRESSIVE WOMEN AFTER PARTICIPATION IN A CORPORAL PRACTICES PROGRAM (Interdisciplinary Studies Journal, 2024)
The aim of this study was to analyze the perceived benefits of women with depression after participating in a program of body practices carried out in the Unified Health System. This is a descriptive qualitative quasi-experimental study conducted at the Basic Health Unit (UBS) of the municipality of Bozano-RS, with 12 women, adults, sedentary, medicated for depression. The exclusion criterion used was the frequency in the program of body practices of at least 75%. The physical activities program was based on playful activities, consisted of 16 weekly sessions, lasting 50 minutes per meeting. A semi-structured interview was applied interpreted by content analysis. The women had a mean age of 53.08±14.04 and reported that participating in the program contributed to the following aspects: reduction of body pain (n=6); relaxation (n=4); to better understand the disease (n=3); improvement of mood and joy (n=3); to treat depression (n=2 socialization (n= 1); to be more physically active (n=1); to improve health (n=1); greater disposition (n=1); improved agility (n=1). It is concluded that body practice for women diagnosed with depression can provide several benefits in their perception.
Keywords: Depression; Motor Activity; Health care; Quality of life